Water Related Names in the Flint Hills - Sondra Van Meter McCoy; Jan Hults (Symphony in the Flint Hills, 2018)
Features nomenclature of prominent bodies of water located throughout Kansas. (Excerpted from: 1001 Kansas Place Names, Sondra Van Meter McCoy and Jan Hults, published by the University Press of Kansas, 1989.)